2019
DOI: 10.1111/wre.12360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Solanum elaeagnifolium, an invasive problematic weed in Jordan

Abstract: Solanum elaeagnifolium (silverleaf nightshade) is a problematic weed that is common in Jordan and difficult to control. The weed exhibits distinct morphological variations in growth habit, leaf shape, leaf margins, flower colour and presence or absence of spines between individuals among and within populations suggesting genetic differences. Genetic variations among 61 samples of S. elaeagnifolium collected from heavily infested sites in the central Jordan Valley were investigated using six simple sequence rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The control of S. elaeagnifolium is highly challenging due to its vigorous vegetative growth and extensive root system (Qasem et al 2019). Although glyphosate and ammonium sulfate can provide effective control (Gitsopoulos et al 2017), the lack of selectivity of the two herbicides limits their usage for control scenarios such as preemergence and direct spraying.…”
Section: Introductionmentioning
confidence: 99%
“…The control of S. elaeagnifolium is highly challenging due to its vigorous vegetative growth and extensive root system (Qasem et al 2019). Although glyphosate and ammonium sulfate can provide effective control (Gitsopoulos et al 2017), the lack of selectivity of the two herbicides limits their usage for control scenarios such as preemergence and direct spraying.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies documented the morphological and acoustic characteristics of buzzing bees and their host plants, we are still at the early stages of understanding such species-specific interactions at the community level [14,[26][27][28][29]. This is more ecologically relevant in invasive weeds, where pollination success, and consequently seed set, is a driving force in invasion success.…”
Section: Introductionmentioning
confidence: 99%
“…Despite genetic diversity studies on introduced S. elaeagnifolium populations in different geographic locations, including Europe, Australia, and South America (Chiarini et al 2018;Qasem et al 2019;Zhu et al 2012Zhu et al , 2013aZhu et al , 2013b, the available genetic marker resource for the species remains limited. Previous research to evaluate the transferability of SSR markers from related Solanum species identified 13 out of 35 SSRs that can amplify targets in S. elaeagnifolium, although only 6 were polymorphic.…”
Section: Introductionmentioning
confidence: 99%